Myelomatous pleural effusion developing after autologous stem cell transplantation in a patient with multiple myeloma: A rare case - Ak Müzeyyen Aslaner; Figen Barut (Wolters Kluwer Medknow Publications, 2023)
Myelomatous pleural effusion (MPE) is a very rare condition with a poor prognosis. In our case of multiple myeloma (MM) with early recurrence presenting with a MPE, management of the treatment is discussed together with the case presentation. A 35 year old female patient with a diagnosis of lambda light chain MM presented with complaints of dyspnea and pain in the left shoulder 2 months after autologous transplantation. On physical examination, respiratory sounds were decreased in the lower lobe of the left lung and there was dullness. Pleural effusion and plasmacytoma, more prominent on the left, were detected on chest X ray and thorax computed tomography (CT). The pleural fluid collected during therapeutic thoracentesis was examined by flow cytometry, cytology, and peripheral smear examination and as a result, the patient was considered to have early recurrence after autologous transplantation, DRd chemotherapy was immediately started, and clinical and radiological improvement was observed. Pleural effusion developing in patients with MM should be evaluated in terms of MPE. In the presence of MPE, the duration of response to treatment is short, thus effective and dynamic treatment methods for bridging should be used before referral of the patients to clinical trials and hematopoietic stem cell transplantation.